Hegemoni Politik-Ekonomi di Kerinci Pada Masa Hindia-Belanda 1904-1942 - Selvi Nurtinta Mardi; Zulqaiyyim Zulqqaiyyim; Nopriyasman Nopriyasman (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2022)
The purpose of this essay is to illustrate how the Kerinci people dealt with the political and economic hegemony that existed in this region during the Dutch East Indies period. The political-economic history category includes this article. This study demonstrates that the Kerinci people have responded to the Dutch East Indies government, as seen by their conflict with the Dutch Colonial Government (the Depati Parbo War and the resistance of the Kerinci clerics). New trade routes that were used by the Kerinci people to escape trade routes that the Dutch had previously dominated have also emerged. The reaction of the Kerinci populace to new trade goods introduced by the Dutch East Indies government, such as tea in the Kayu Aro region and Kayu Manis in Bukit Barisan, as well as the opening of a school in Kerinci.Keywords: Coffie, Rice, Tea, New Line